The generalized Alchian-Allen theorem - Junichi Minagawa; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
The Alchian-Allen substitution theorem states that an increase of the prices of two similar goods by the same amount leads to a relative increase in the compensated demand of the more expensive good. In this paper we generalize this theorem to ordinary demand functions and show under which conditions the Alchian-Allen result continues to hold when income and endowment effects are taken into account.
Keywords: D11; 330; the Alchian-Allen theorem; income and endowment effects